Coordinating China and DAC development partners: challenges to the aid architecture in Rwanda - Sven Grimm; Heike Höß; Katharina Knappe; Marion Siebold; Johannes Sperrfechter (Deutsches Institut für Entwicklungspolitik (DIE), 2011)
The international development debate has been marked by two major trends in recent years: intensified discussions on the effectiveness of aid, and the proliferation of actors involved in international cooperation. This study aims to contribute to the debate on aid effectiveness by exploring challenges to DAC and non-DAC development partner (DP) coordination at country level, with Rwanda serving as the country case. A detailed mapping of development assistance to Rwanda provides the necessary basis for the study. German engagement is taken as an example of a DAC development partner, while China is the key example for the engagement of a non-DAC partner. This study shows that Rwanda's government, despite its aid dependency, demonstrates strong ownership of its development agenda. However, the Rwandan government has clearly not been successful in integrating China into its aid coordination architecture. The study argues that the lack of integration of non-DAC DPs – not least so China – is a major challenge to the country's aid architecture if the leverage over DAC partners is to be maintained. The recommendations made by this study address the three key actors examined: the Government of Rwanda, Germany, and China.
Keywords: 330; Entwicklungshilfe; Performance-Messung; Entwicklungshilfe; Entwicklungspolitik; Ruanda; Deutschland; China